Program Kreativitas Mahasiswa Pembuatan Hand Grip Modern Untuk Bandminton Tahun 2021 - Achamd Zakaria; Restian Gigih Sejati; Slamet Riyadi (Pusat Riset dan Inovasi Nasional, 2021)
The aim of this research is to create a racket grip modification product to improve grip techniques in badminton. The research approach used is development research. The results of the research obtained a value for aspect 1 regarding